Gene encoding the 37,000-dalton minor sigma factor of Bacillus subtilis RNA polymerase: isolation, nucleotide sequence, chromosomal locus, and cryptic function. - Duncan, M L (1987)
We began an analysis of rpoF, the gene encoding the cryptic, 37,000-dalton minor sigma factor (sigma-37) of Bacillus subtilis RNA polymerase. Using antibody raised against sigma-37 holoenzyme to probe a lambda gt11 expression vector library, we isolated a 901-base-pair EcoRI fragment that expressed the COOH-terminal half of sigma-37 fused to lacZ. We used this fragment as a hybridization probe to isolate the entire rpoF gene and additional flanking sequences. Identity of the cloned gene was confirmed by the size and immunological reaction of its product expressed in Escherichia coli and, after DNA sequencing, by the homology of its predicted product (264 residues; 30,143 daltons) with other sigma factors. The DNA sequence also suggested that rpoF may lie in a gene cluster. Upstream of rpoF was an open reading frame that would encode a protein of 17,992 daltons; this frame overlapped the rpoF-coding sequence by 41 base pairs. Immediately following rpoF was a reading frame that would encode a protein of at least 20,000 daltons; expression of this region may be translationally coupled to that of rpoF. By plasmid integration and PBS1 transduction, we found the chromosomal locus of rpoF linked to ddl and dal at 40 degrees on the B. subtilis map and near no known lesions affecting growth regulation or development. Further, an rpoF null mutation resulting from gene disruption had no effect on cell growth or sporulation in rich medium, suggesting that sigma-37 may partly control a regulon not directly involved in the sporulation process.